Play in Primary School Market in the Garden: Learn to Understand Entrepreneurship - Chantanapim, Wimonlak (Asia Research Network Journal of Education, 2023)
Entrepreneurship is key success of finding new ways to create value. However, many people wonder whether entrepreneurial skills and mindset can be effectively taught in childhood. This paper will highlight the activity of primary school market in the garden (PMG). The author as participant observer (a teacher) in Khon Kaen University Demonstration Primary School clarified what the PMG look like and how it situated students to learn via role playing for developing entrepreneurship. The PMG is usually organized for a month. The activities included 1) students plan their business for a day of market in the garden, 2) students present their business plans into the class, 3) students develop products for selling with parents’ helping, 4) students design the packages and determine the price, 5) students design their marketing plan, and 6) students practice their selling products as participating in a day of market in the garden. Power of playing in primary school market in the garden (PMG) is a context-based experiential learning program that helps Grades 1-6 students explore their passions, talents and interests as they plan and implement their own real business ventures. It may also enhance students to perceive some issues related to entrepreneurial skills.